The Implementation of Modern Learning Methods in Memorizing the Qur'an (An Alternative to Conventional Methods) - Azzakiyah, Lailatul Fithriyah; Zulian, Pradana Boy; Bachtiar, Hasnan; Jahro, Nasihatud Diniyah (STAI Publisistik Thawalib Jakarta, 2025)
Conventional methods for teaching Qur'anic memorisation (tahfizh) remain limited in accommodating the diverse learning styles of students and lack integration of modern learning theories that are more creative and engaging. This study aims to propose a novel concept for teaching Qur'anic memorisation by applying Hemisphere Theory, Multiple Intelligences, and Mind Mapping to address existing gaps in knowledge. The research methodology employed a descriptive-analytical approach through a literature review, gathering primary and secondary data from books, journals, and scholarly documents, followed by data analysis, interpretation, and generalisation. The findings reveal that this study presents an innovative approach to Qur'anic memorisation by comprehensively integrating modern learning concepts that had not been previously applied. The primary advantage lies in the combined application of Multiple Intelligences, Brain Hemisphere Theory, and Mind Mapping within the tahfizh process. This method is designed to be more understandable, enjoyable, and suitable for various age groups, distinguishing it from conventional methods, which tend to be rigid and less engaging. This approach emphasises rote memorisation and enhances students' comprehension and memory retention more creatively and adaptively tailored to individual needs. In conclusion, the innovation of Qur'anic learning methods incorporating modern theories such as Brain Hemisphere, Multiple Intelligences, and Mind Mapping is essential to overcome boredom, increase comfort, and encourage more in-depth research in the future.